Penguatan Fungsi Legeslasi Dewan Perwakilan Daerah Republik Indonesia Dalam Pembahasan Rancangan Undang-Undang - Dediansyah, Ahmad (Journal of Education, Humaniora and Social Sciences (JEHSS), 2019)
This study aims to determine the position of the functions and authority of the Regional Representative Council based on the 1945 Constitution of the Republic of Indonesia and the urgency of strengthening the function of the Regional Representative Council as a regional representative in national policy making at the central level. The research method used is a normative legal research method that focuses on library research, namely the search for legal materials consisting of primary legal materials, secondary legal materials, and tertiary legal materials. to obtain secondary data from legal materials. The normative approach is carried out by reviewing the provisions or regulations in force. Basically, the existence of the Regional Representative Council through an amendment to the 1945 Constitution of the Republic of Indonesia is based on the existence of 2 (two) factors, namely democratization and efforts to accommodate regions in making national policies, theoretically the existence of the Regional Representative Council is intended to apply the principle of checks and balances between state institutions, namely the process of mutual supervision and balance between State institutions. This was done to strengthen central and regional relations in order to maintain the integrity and unity of the unitary state of the Republic of Indonesia. However, based on the amendment results of the 1945 Constitution of the Republic of Indonesia the authority of the Regional Representative Council to carry out its function as a regional representative is still inadequate, so the desire to implement the principle of checks and balances between State institutions is still not realized.